2015
DOI: 10.1039/c5ra00083a
|View full text |Cite
|
Sign up to set email alerts
|

Molecular level interactions in binary mixtures of 1-ethyl 3-methylimidazolium tetrafluoroborate and water

Abstract: NIR spectroscopic analysis and DLS measurements were carried out to study hydrogen bonding and aggregation in ionic liquid–water binary mixtures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…31 Marium and co-workers reported the presence of large aggregated clusters of [C 2 mim][BF 4 ] in its binary mixtures with water, having an average correlation diameter of ∼354− 900 nm. 32 This work investigates the prospect and extent of the longrange density fluctuation in various binary mixtures of ILs themselves. Binary mixtures of two ILs have relatively been a very new field, with a little to no concrete understanding on their physicochemical, dynamical, and structural aspects.…”
Section: Introductionmentioning
confidence: 99%
“…31 Marium and co-workers reported the presence of large aggregated clusters of [C 2 mim][BF 4 ] in its binary mixtures with water, having an average correlation diameter of ∼354− 900 nm. 32 This work investigates the prospect and extent of the longrange density fluctuation in various binary mixtures of ILs themselves. Binary mixtures of two ILs have relatively been a very new field, with a little to no concrete understanding on their physicochemical, dynamical, and structural aspects.…”
Section: Introductionmentioning
confidence: 99%
“…For C 2 ImHSO 4 - w 0 , no texture was observed over the measured hydration range (5 ≤ w 0 ≤ 80) (Figure b). DLS measurements suggested that C 2 ImHSO 4 - w 0 also formed an L 1 solution. , As shown in Figure b, the hydrodynamic diameter of [C 2 MIm]­[HSO 4 ] micelles was determined to be 0.6 nm, which was smaller than that of [C 14 MIm]­[HSO 4 ]. Larger micelles corresponding to sizes of 255.1 and 531.1 nm were observed for C 2 ImHS-60 and C 2 ImHSO 4 -30, respectively.…”
Section: Resultsmentioning
confidence: 91%
“…DLS measurements suggested that C 2 ImHSO 4 -w 0 also formed an L 1 solution. 24,25 As shown in Figure 2b According to weight fractions and densities, the calculated thicknesses of the water layer decreased from 2.41 to 1.48 nm (Table S1 of the Supporting Information). The 2D 1 H NMR spectrum (Figure S1d of the Supporting Information) suggested that imidazolium rings aggregated to form an interdigitated bilayer structure.…”
Section: ■ Experimental Sectionmentioning
confidence: 92%
“…The thermophysical and thermodynamic properties of [EMIM] + [BF 4 ] − and their binary mixtures with water, acetone, acetonitrile, DMSO, DMF, DMA, 2-ethoxyethanol, 2.2.2trifluoroethanol, , cyclopentanone, cyclohexanone, methyl ethyl ketone, 2-pyrrolidone, 1-methyl-2-pyrrolidone, ,, aniline, N -methyl aniline, and 2-methyl aniline , have been reported in the literature at various temperatures. The binary mixtures reported for [EMIM] + [MeSO 4 ] − in the literature are with alcohols (C 1 –C 9 ) and water, , and also, binary mixtures of [EMIM] + [MeSO 4 ] − with acetic and propionic acid are reported in the literature at temperatures of 298.15–318.15 K .…”
Section: Introductionmentioning
confidence: 99%